Self Management of Type 2 Diabetes Mellitus Patients at The Internist Polyclinic of Ngudi Waluyo General Hospital Blitar Distric - Ulfa Husnul Fata; Ila Ageng Safiani; Laily Prima Monica; Maria Ulfa; Wahyu Wibisono (Journal of Ners and Midwifery, 2022)
Type 2 Diabetes Mellitus is a disease that can cause many complications. Some of the problems that can arise in patients with Type 2 Diabetes Mellitus, one of the causes is low self-management behavior.This study aims to determine self-management in patients with type 2 diabetes mellitus. This research is a descriptive study. The variable in this study was self-management in type 2 diabetes mellitus patients. This research was a descriptive study. The population in this study were all type 2 diabetes mellitus patients who routinely exercised control at the Internal Medicine Polyclinic at Ngudi Waluyo Wlingi Hospital, Blitar Regency in December 2021, namely 156 people. The sample in this study based on the sample size formula was 112 people with a sampling technique, namely purposive sampling with regard to inclusion and exclusion criteria. This research was conducted from January to February 2022 at the Internal Medicine Clinic at Ngudi Waluyo Wlingi Hospital, Blitar Regency. Data collection in this study used general data instruments consisting of age, gender, routine control, level of education, and duration of DM. Specific data questionnaire using the SDMQ Questionnaire (Diabetes Self Management Questionnaire) which consists of 16 questions with several subdomains in it. The results of this study indicated that 69.6% (78 respondents) had good category of self-management and 30.4% (34 respondents) had sufficient category of respondents. It is hoped that the results of this study can be used as a form of input for health workers, especially nurses, in carrying out their roles as educators and counselors to improve self-management in type 2 diabetes mellitus patients to improve quality of life and prevent complications.